Development of the QUIZIZZ Platform as an Interactive Quiz-Based Learning Media for Arabic Language Lessons at Madrasah IBTIDAIYAH - Hanif, Akhyar; ., Herman; Mudinillah, Adam; Rahmi , Putri Windi Lailatur (International Journal of Membrane Science and Technology, 2023)
This era is full of technology. The use of online learning media is an alternative used by educators to create a learning atmosphere that is not monotonous by displaying animated images so that students do not feel bored. One of the online media used during the learning process is the use of the Quiziz platform. This study aims to develop the quiziz platform as an alternative medium in interactive quiz-based Arabic learning for Madrasah Ibtidaiyah students. Quiziz is an online based game making platform. The research method uses the development method with the Dick and Carey model where the aim of this model is to become a systematic learning process. The purpose of this study was to determine the development of the Quiziz platform as an interactive quiz in learning Arabic at Madrasah Ibtidaiyah. The conclusion of this study explains that the Quiziz platform can assist teachers in creating online-based interactive quizzes and student achievement increases after using the Quiziz platform in the teaching and learning process. The limitation of this research is that the researcher only conducted research on the Quiziz platform as an interactive quiz for Islamic elementary schools, therefore, the researcher hopes that future researchers will be able to conduct research using the same platform, but more developed in other educational units so that research becomes interesting.